Peramalan Trend Pendapatan di Toko Online XYZ Menggunakan Single Moving Average - Gustin, Jonathan Nandika; Pakereng, Magdalena A. Ineke (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
The Utilization of an online shopping platform as a place to sell products produces sales transaction data. This makes it a reference to predict income trends for nine months, by taking a case study on the Serenade Home Décor online store. The method used to predict is Single Moving Average. Single Moving Average is a technic of calculating the average of a number from the latest actual value, updated as new available values, and used to make predictions in subsequent periods. Results of the study using Moving Average are 3, 5, and 9, which can produce an income value of Rp. 3,103,716.00, and results in an accuracy value of 66.74382%, and the MAPE value obtained is quite good at 33.85618%, which means that the method used is still quite good. It would be better if use more than one method, which will be able to make comparisons of the prediction, result, and accuracy.